Tribological Analysis of Laser-Textured WC-Co Against Ti6Al4V Under Dry and Lubricated Conditions for Different Sliding Times - Javier Garcia-Fernandez; Moises Batista; Juan Manuel Vazquez-Martinez; Jorge Salguero; Irene Del Sol; Magdalena Ramirez-Peña (Lubricants)
Machining titanium alloys, particularly Ti6Al4V, pose significant challenges in manufacturing engineering. The combination of high strength and low thermal conductivity makes Ti6Al4V a particularly difficult material to machine. One of these difficulties is the rapid wear and short tool life of cutting tools, which substantially increases manufacturing costs. To address this issue, the texturing of cutting tools, especially using laser-based techniques, has garnered significant attention due to its potential to enhance the tribological performance of textured surfaces. In this paper, by means of a groove design applied to a tungsten carbide (WC) disc by laser surface texturing (LST), its behavior and wear have been evaluated after subjecting it to tribological pin-on-flat tests by confronting it with Ti6Al4V pins with different reciprocating times (250 s, 500 s, 750 s and 1000 s) in lubricated and dry conditions. In addition, these same tests have been replicated without textures for comparison. Through conducting this research, we expect to gain new insights into texturing processes and their influence on friction and sliding behavior under lubricated conditions. Additionally, the study aims to evaluate how lubricant retention capacity varies to reduce friction and wear across different testing durations. The results show better behavior with textures, reaching a higher rate of volume loss in the titanium pins. The main conclusions obtained after these tests are that textures offer a better performance in tests up to 800 s. In addition, after this time, the lubricant begins to lose its properties, becoming an abrasive paste.